2016
DOI: 10.1007/s12032-016-0746-8
|View full text |Cite
|
Sign up to set email alerts
|

The role of postoperative adjuvant chemotherapy for lymph node-positive esophageal squamous cell carcinoma: a propensity score matching analysis

Abstract: The prognosis of patients with lymph node-positive esophageal squamous cell carcinoma (ESCC) who primarily receive radical esophagectomy remains poor. In this study, we aimed to retrospectively investigate the role of postoperative adjuvant chemotherapy with docetaxel- or paclitaxel-based regimens in these patients. A total of 434 consecutive patients were included in this study who underwent radical esophagectomy and were pathologically confirmed to have lymph node-positive ESCC from January 2005 to December … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
26
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(30 citation statements)
references
References 26 publications
4
26
0
Order By: Relevance
“…These results were consistent with other reports (6,7). Recently, Rong et al have also reported that the group receiving adjuvant chemotherapy with docetaxel-or paclitaxel-based regimens had significantly longer median DFS than the surgery-alone group; however, there was no significant difference in the OS of these groups (8). The effects of preoperative chemotherapy are being evaluated in randomized trials.…”
supporting
confidence: 91%
See 1 more Smart Citation
“…These results were consistent with other reports (6,7). Recently, Rong et al have also reported that the group receiving adjuvant chemotherapy with docetaxel-or paclitaxel-based regimens had significantly longer median DFS than the surgery-alone group; however, there was no significant difference in the OS of these groups (8). The effects of preoperative chemotherapy are being evaluated in randomized trials.…”
supporting
confidence: 91%
“…On the other hand, potential disadvantages include the morbidity and mortality associated with toxicity, disease progression with the selection of drug-resistant tumor clones, and the delay of definitive surgical treatment (15). With regard to the survival benefit of postoperative adjuvant chemotherapy, previous reports (5)(6)(7)(8) have shown that adjuvant chemotherapy improves disease-free survival; however, these reports did not result in significant differences in OS as compared with surgery alone. Lyu based adjuvant chemotherapy improved the OS of patients with lymph node-positive thoracic esophageal squamous cell carcinoma as compared with surgery alone (16).…”
Section: Discussionmentioning
confidence: 99%
“…In 2016, Qin et al . from China assessed the efficacy of adjuvant chemotherapy in 434 stage II–III ESCC patients with positive lymph nodes confirmed by postoperative pathology and concluded that adjuvant chemotherapy could improve DFS of pN1 ESCC patients and those with tumors < 4.5 cm, as well as OS in patients with positive lymph nodes …”
Section: Discussionmentioning
confidence: 99%
“…43) Lee et al 44) and Zhang et al 45) also reported similar results. Recently, Rong et al 46) also reported that the group given adjuvant chemotherapy with docetaxel-or paclitaxel-based regimens had a significantly longer median DFS than that in the surgery alone group but resulted in no significant difference in OS between these groups. The effects of preoperative chemotherapy are being evaluated in randomized trials.…”
Section: Neoadjuvant and Adjuvant Chemotherapymentioning
confidence: 99%